1998
DOI: 10.1002/(sici)1097-0320(19980701)32:3<223::aid-cyto9>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

In situ subcellular localization of epitope‐tagged human and rabbit carboxylesterases

Abstract: Carboxylesterases are a ubiquitous class of enzymes thought to be involved in xenobiotic metabolism and detoxification. Primary amino acid sequence data suggest that these proteins localize to the endoplasmic reticulum. However, since this family of proteins is highly homologous, the generation of specific reagents to monitor expression and subcellular localization has been unsuccessful. To accomplish in situ detection of a human alveolar macrophage carboxylesterase and a rabbit liver carboxylesterase, we cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is converted in vivo to SN-38 (7ethyl-10-hydroxy-camptothecin), the active metabolite that causes cell death 7 , by human liver CES-2. The process of conversion is very important, since SN-38 is 300-2000 times more potent than irinotecan in vitro and in vivo [13][14][15][16][17][18] . It has been reported that patients with high CES-2 mRNA expression levels in peripheral blood mononuclear cells present a higher activation ratio of irinotecan to SN38 7 .…”
Section: Discussionmentioning
confidence: 99%
“…It is converted in vivo to SN-38 (7ethyl-10-hydroxy-camptothecin), the active metabolite that causes cell death 7 , by human liver CES-2. The process of conversion is very important, since SN-38 is 300-2000 times more potent than irinotecan in vitro and in vivo [13][14][15][16][17][18] . It has been reported that patients with high CES-2 mRNA expression levels in peripheral blood mononuclear cells present a higher activation ratio of irinotecan to SN38 7 .…”
Section: Discussionmentioning
confidence: 99%